2020
DOI: 10.22458/urj.v12i2.3144
|View full text |Cite
|
Sign up to set email alerts
|

Insectos asociados al agroecosistema de café bajo sombra en el Distrito de Milpuc, Amazonas, Perú

Abstract: Introducción: Los agroecosistemas de C. arabica bajo sombra son de los cultivos que se consideran no dañinos para la biodiversidad, sin embargo, dada la importancia ecológica que tienen en el resguardo de muchas especies son escasos los estudios en este cultivo en la zona. Objetivo: Proporcionar información sobre la diversidad y la fluctuación de insectos asociados al agroecosistema de café bajo sombra, mediante un estudio faunístico. Métodos: Los insectos se recolectaron sobre diez plantas de C. arabica divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In this sense, Ramos-Patlán et al [11], found that the largest number of individuals and species of mantis are concentrated in sites with significant agricultural activity, mainly in places with high humidity and irrigation that are distributed from the center to the south of the State. In different studies, the refuge potential that agroecosystems offer to insects and small vertebrates have been reported, mainly in traditional agroecosystems where there is tolerance of weed vegetation and managements that promote organic fertility [28]. The diversity patterns showed significant differences between the crops.…”
Section: Insects In Guanajuato's Agroecosystemsmentioning
confidence: 99%
“…In this sense, Ramos-Patlán et al [11], found that the largest number of individuals and species of mantis are concentrated in sites with significant agricultural activity, mainly in places with high humidity and irrigation that are distributed from the center to the south of the State. In different studies, the refuge potential that agroecosystems offer to insects and small vertebrates have been reported, mainly in traditional agroecosystems where there is tolerance of weed vegetation and managements that promote organic fertility [28]. The diversity patterns showed significant differences between the crops.…”
Section: Insects In Guanajuato's Agroecosystemsmentioning
confidence: 99%